2012
DOI: 10.1371/journal.pone.0041305
|View full text |Cite|
|
Sign up to set email alerts
|

Microbial Community Analysis of a Coastal Salt Marsh Affected by the Deepwater Horizon Oil Spill

Abstract: Coastal salt marshes are highly sensitive wetland ecosystems that can sustain long-term impacts from anthropogenic events such as oil spills. In this study, we examined the microbial communities of a Gulf of Mexico coastal salt marsh during and after the influx of petroleum hydrocarbons following the Deepwater Horizon oil spill. Total hydrocarbon concentrations in salt marsh sediments were highest in June and July 2010 and decreased in September 2010. Coupled PhyloChip and GeoChip microa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
122
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(136 citation statements)
references
References 65 publications
11
122
1
Order By: Relevance
“…Bacterial bioremediation of marine oil spills is still present in the public consciousness due to the ongoing discussions about compensation and responsibilities connected to the environmental ca- tastrophe of the Deepwater Horizon oil spill in the Gulf of Mexico 3 years ago (31)(32)(33). Here and in other marine environments polluted by crude oil, marine hydrocarbonoclastic bacteria such as A. borkumensis were detected as key players in bioremediation (34)(35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial bioremediation of marine oil spills is still present in the public consciousness due to the ongoing discussions about compensation and responsibilities connected to the environmental ca- tastrophe of the Deepwater Horizon oil spill in the Gulf of Mexico 3 years ago (31)(32)(33). Here and in other marine environments polluted by crude oil, marine hydrocarbonoclastic bacteria such as A. borkumensis were detected as key players in bioremediation (34)(35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…Initially, some DWH spill researchers proposed a swift microbial response (16,17) because microbes have the capacity to degrade constituent carbon compounds in oil (31)(32)(33)(34)(35) and earlier nutrient enrichment, metal exposure, and oiling experiments provided evidence that marsh communities could withstand low levels of disturbance from an oil spill (25,36). Short-duration studies based on research conducted during one sampling time or from Ͻ6 to 9 months of sampling events in 2010 and 2011 confirmed that the relative abundances and species richness for bacterial communities exposed to weathered oil residues changed through time and recognized a greater diversity among known hydrocarbon-degrading bacteria as the amount of petroleum hydrocarbon concentrations increased (37)(38)(39)(40). Although a cascading series of long-term biogeochemical consequences, due to the microbial response, was anticipated for the marsh ecosystem (41), some of the earlier studies suggested a faster-than-expected recovery (16,42).…”
mentioning
confidence: 93%
“…We expected that the PAH compound concentrations would generally decrease as the molecular weight increased because the half-lives for LMW PAH compounds, which have higher volatility and enhanced bioavailability, range from ϳ10 to 120 days, and the half-lives for high-molecular-weight (HMW) compounds, like BaP, range from 200 to Ͼ1,400 days (71). We also expected that biodegradation should have decreased PAH levels from the time of initial oiling (35,37,72). However, the concentration of PAH compounds increased over time, and the molecular ratios of key PAHs indicated that the source(s) also changed (see Fig.…”
mentioning
confidence: 99%
“…The first characteristic of oil spill is the increase of concentrations of total petroleum hydrocarbons in seawater, soils in coastal areas such as salt marshes, fish muscle and sandy beach micro benthic community (Jung et al, 2011;Yu et al, 2013). It will result in the complete mortality of plants, Spartina alterniflora and Juncus roemerianus, as well as changes of the microbial community, vegetation structure, biomass and function of salt marshes in the coastal ecosystem (Beazley et al, 2012;Lin and Mendelssohn, 2012;Lamendella et al, 2014). Oil spills have affected the wetlands such as in Mississippi River Delta Ecosystem, which has further influenced fish production, oil and gas supply in the wetlands .…”
Section: Metal Contaminationmentioning
confidence: 99%